2013
DOI: 10.1136/archdischild-2012-302941
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of milk type consumed and weight status in preschoolers

Abstract: Objective Evaluate relationships between type of milk consumed and weight status among preschool children. Design Longitudinal cohort study. Setting Early Childhood Longitudinal Study–Birth Cohort, a representative sample of U.S. children. Participants 10,700 U.S. children examined at age 2 and 4 years. Main Outcome Measures BMI z-score and overweight/obese status as a function of milk type intake. Results The majority of children drank whole or 2% milk (87% at 2 years, 79.3% at 4 years). Across raci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 30 publications
1
55
1
1
Order By: Relevance
“…9 Servings of milk were similarly defined as equating to 8-ounce servings and quantified in terms of frequency by the same scale as described for SSB, as reported previously. 22 Direct measurements of height and weight were obtained by trained researchers by using a standardized protocol. The children were dressed in light clothing and did not wear shoes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Servings of milk were similarly defined as equating to 8-ounce servings and quantified in terms of frequency by the same scale as described for SSB, as reported previously. 22 Direct measurements of height and weight were obtained by trained researchers by using a standardized protocol. The children were dressed in light clothing and did not wear shoes.…”
Section: Methodsmentioning
confidence: 99%
“…21,22 The NCES ethics review board approved the study, and all participants gave informed consent. The ECLS-B was designed by NCES to examine a large range of influences on childhood early experiences.…”
Section: Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, two cohort studies in young children (Scharf et al, 2013) and adolescents (Berkey et al, 2005) showed that children or adolescents consuming low fat milk had a similar increase in body weight as those consuming full fat. Refined grains were omitted since they are counterbalanced with whole grains.…”
Section: Discussionmentioning
confidence: 99%